Time variation in an optimal asymmetric preference monetary policy model - Cassou, Steven P.; Vázquez, Jesús (My University, 2013)
This paper considers a time varying parameter extension of the Ruge-Murcia’s (Ruge-Murcia, F. J. 2003. “Does the Barro-Gordon Model Explain the Behavior of us Inflation? A Reexamination of the Empirical Evidence.” Journal of Monetary Economics 50: 1375–1390; Ruge-Murcia, F. J. 2004. “The Inflation Bias When the Central Bank Targets the Natural Rate of Unemployment.” European Economic Review 48: 91–107.) model to explore whether some of the variation in parameter estimates seen in the literature could arise from this source. A time varying value for the unemployment volatility parameter can be motivated through several means including variation in the slope of the Phillips curve or variation in the preferences of the monetary authority. We show that allowing time variation for the coefficient on the unemployment volatility parameter improves the model fit and it helps to provide an explanation of inflation bias based on asymmetric central banker preferences, which is consistent across subsamples.
Keywords: Asymmetric preferences; Conditional unemployment volatility; Time varying parameter